A Physical Model-Based FDTD Field-Circuit Co-Simulation Method for Schottky Diode Rectifiers - Hongzheng Zeng (IEEE Access, 2019)
So far, plenty of microwave power circuits such as microwave diode rectifiers are mainly designed and analyzed by conventional electromagnetic (EM) co-simulation method based on the semiconductor equivalent circuit models. However, the simplified equivalent circuit model may contribute to loss of precision at high frequencies or under high power. Compared with the equivalent circuit model, the semiconductor physical model provides a means for studying the physics of electron transport, and thus, better describes the semiconductor device. This paper explores analyzing microwave diode rectifiers by employing a physical model-based field-circuit co-simulation method. This method combines the physical model-based circuit simulation to the finite-difference time-domain (FDTD)-based field-circuit co-simulation and thus, achieves accurate and effective hybrid full-wave field-circuit co-simulation. For validation, two diode rectifiers working at S- and C-band, respectively, are simulated and analyzed by the proposed method. The simulation result agrees well with measurement and shows higher accuracy than the equivalent circuit model-based simulation.